EFEKTIFITAS LAYANAN BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING TERHADAP PERUBAHAN SIKAP BELAJAR SISWA - Rahman, Deni; Fitriani, Wahidah (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The main problem in this study is how to change students' learning attitudes in a positive direction through role playing technique group guidance services. The aim of the study was to see whether or not the role playing technique group guidance services were significant to changes in student learning attitudes. The research method used is the experimental method, namely research that aims to see changes in student learning attitudes with group guidance services using role playing techniques. The type of design used in this study is a Quasi-Experimental design with a one group pretest-posttest design. The topics discussed in the role playing technique group guidance service are attitudes towards teachers, students' attitudes towards lesson objectives, attitudes towards assignments given by the teacher, and good attitudes in learning. The results showed that there was a significant change in students' learning attitudes toward a better direction